2015
DOI: 10.1590/s1415-475738138120140132
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced tethered-flight duration and locomotor activity by overexpression of the human gene SOD1 in Drosophila motorneurons

Abstract: Mutation of the human gene superoxide dismutase (hSOD1) is associated with the fatal neurodegenerative disease familial amyotrophic lateral sclerosis (Lou Gehrig’s disease). Selective overexpression of hSOD1 in Drosophila motorneurons increases lifespan to 140% of normal. The current study was designed to determine resistance to lifespan decline and failure of sensorimotor functions by overexpressing hSOD1 in Drosophila‘s motorneurons. First, we measured the ability to maintain continuous flight and wingbeat f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Among commonly used assays for assessing healthspan are those that measure movement. These include the negative geotaxis assay for evaluating climbing ability, [31][32][33] and a variety of flight duration, 33,34 and exploratory activity tests. 33,35,36 The movement weakening during aging may be due to skeletal muscle deterioration or cognitive decline and can be further examined using histological T A B L E 1 Suggested assays in Drosophila to investigate traits that contribute to healthspan in humans methods.…”
Section: Applying Fly-specific Assays To the Understanding Of Humanmentioning
confidence: 99%
“…Among commonly used assays for assessing healthspan are those that measure movement. These include the negative geotaxis assay for evaluating climbing ability, [31][32][33] and a variety of flight duration, 33,34 and exploratory activity tests. 33,35,36 The movement weakening during aging may be due to skeletal muscle deterioration or cognitive decline and can be further examined using histological T A B L E 1 Suggested assays in Drosophila to investigate traits that contribute to healthspan in humans methods.…”
Section: Applying Fly-specific Assays To the Understanding Of Humanmentioning
confidence: 99%
“…In our study, knockdown of AGO1 and piwi genes in the nervous system and the fat body caused activation of stress response genes, especially antioxidant defense genes (Sod1, Prx5), genes of DNA damage response and repair (Gadd45, spn-B), and genes encoding heat shock proteins (Hsp27, Hsp68). Several of these genes have been identified previously as pro-longevity genes [33][34][35]42,43]. At the same time, suppression of AGO2 and AGO3 expression mainly reduced the activity of stress response genes.…”
Section: Discussionmentioning
confidence: 87%
“…In addition, changes in the levels of retrotransposons and expression of stress response genes were analyzed to determine the molecular mechanisms involved. It was previously found that genes of antioxidant defense, DNA damage response, and repair play a critical role in both lifespan regulation and the reaction of cells, tissues, and a whole organism to ionizing irradiation [33][34][35][36][37][38][39][40][41]. In addition, genes involved in different mechanisms of proteostasis demonstrate changes during aging and after irradiation as well [38,39,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In our study, knockdown of AGO1 and piwi genes in the nervous system and the fat body caused activation of stress response genes, especially antioxidant defense genes ( Sod1, Prx5 ), genes of DNA damage response and repair ( Gadd45, spn-B ), and genes encoding heat shock proteins ( Hsp27, Hsp68 ). Several of these genes have been identified previously as pro-longevity genes [ 33 , 34 , 35 , 42 , 43 ]. At the same time, suppression of AGO2 and AGO3 expression mainly reduced the activity of stress response genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, changes in the levels of retrotransposons and expression of stress response genes were analyzed to determine the molecular mechanisms involved. It was previously found that genes of antioxidant defense, DNA damage response, and repair play a critical role in both lifespan regulation and the reaction of cells, tissues, and a whole organism to ionizing irradiation [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 ]. In addition, genes involved in different mechanisms of proteostasis demonstrate changes during aging and after irradiation as well [ 38 , 39 , 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%